Supply chain disruption and energy supply shocks: Impact on euro area output and prices - Roberto A. De Santis (European Central Bank (ECB), 2024)
We identify jointly supply chain disruptions shocks and energy supply shocks together with demand shocks using a structural BVAR with narrative restrictions. The impact of adverse supply chain disruption shocks on inflation expectations and core HICP is strong and rather persistent, while the impact is small and transitory after energy supply shocks. Supply chain disruption shocks and favourable demand shocks explain the large faction of output fluctuations in the 2020-2022 period. The dynamics of core prices and inflation expectations are instead mostly explained by supply chain disruption shocks and to a lesser extent by adverse energy supply shocks.
Keywords: C32; E32; 330; Supply chain disruption shocks; energy supply shocks; inflation expectations; SVAR; narrative identification